Private Health Policy Toolkit for Africa : Tools for Engaging the Private Health Sector - World Bank Group (World Bank, Washington, DC, 2016)
There is growing recognition that the private health sector is a significant source of health care in most African countries. According to "Healthy Partnerships: How Governments Can Engage the Private Sector to Improve Health in Africa" (2010), the private sector share of total health expenditure in Sub-Saharan Africa is on average 51 percent. Use of the private health sector in Africa is particularly strong among groups that policymakers most want to reach, including the poor, women, children, and people with diseases such as tuberculosis, malaria, and human immunodeficiency virus (HIV). The tools presented in this report help readers design strategies and approaches for engaging the private sector in a health system. Topics are organized into five modules outlining specific activities that can expand and tighten private health sector engagement leading to sustainable, pro-poor change.